Flux response of glycolysis and storage metabolism during rapid feast/famine conditions in Penicillium chrysogenum using dynamic 13C labeling - De Jonge, Lodewijk; Buijs, Nicolaas A. A.; Heijnen, Joseph J.; Van Gulik, Walter M.; Abate, Alessandro; Wahl, Sebastian Aljoscha (Biotechnology Journal, 2014)
The scale-up of fermentation processes frequently leads to a reduced productivity compared to small-scale screening experiments. Large-scale mixing limitations that lead to gradients in substrate and oxygen availability could influence the microorganism performance. Here, the impact of substrate gradients on a penicillin G producing Penicillium chrysogenum cultivation was analyzed using an intermittent glucose feeding regime. The intermittent feeding led to fluctuations in the extracellular glucose concentration between 400 μM down to 6.5 μM at the end of the cycle. The intracellular metabolite concentrations responded strongly and showed up to 100-fold changes. The intracellular flux changes were estimated on the basis of dynamic 13C mass isotopomer measurements during three cycles of feast and famine using a novel hybrid modeling approach. The flux estimations indicated a high turnover of internal and external storage metabolites in P. chrysogenum under feast/famine conditions. The synthesis and degradation of storage requires cellular energy (ATP and UTP) in competition with other cellular functions including product formation. Especially, 38% of the incoming glucose was recycled once in storage metabolism. This result indicated that storage turnover is increased under dynamic cultivation conditions and contributes to the observed decrease in productivity compared to reference steady-state conditions. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2022-01-11
Keywords: Dynamic conditions; In vivo enzyme kinetics; P. chrysogenum; Systems biology